Counterfeiting : Fake Goods Production and its Impact on the Market of Luxury Brands in the U.S.A. and China - Choizhalsanova, Ariuna (2021)
Proliferation of counterfeiting in the industry of luxury brands is a serious issue in the modern economy that has a substantial impact on brands and consumers alike. Previous researchers have pointed out, mainly through survey analyses, the main reasons on why counterfeiting is in demand among the consumers as well as on how counterfeiters proliferate and competete with luxury brands. This bachelor thesis attempts to comprehend past research both on supply level of counterfeiting, production and distribution, but also on demand level, consumers’ typology and their motivations to buy luxury imitations. To find out how luxury brands deal with its counterfeited competitors on the market, a luxury brand, Louis Vuitton case is studied, its practices and measures against counterfeiting.